1981
DOI: 10.1042/cs0610585
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Individual Organ Release of Noradrenaline Measured by An Improved Radioenzymatic Technique; Limitations of Peripheral Venous Measurements in the Assessment of Sympathetic Nervous Activity

Abstract: 1. The validity of plasma noradrenaline as an index of sympathetic nervous activity was assessed by estimating variation in individual organ contribution to circulating concentrations.2. Arteriovenous (A-V) differences in noradrenaline and adrenaline concentration were measured across several organs in nine patients with mild essential hypertension, in five with renal artery stenosis and 15 phaeochromocytoma patients.3. In patients with phaeochromocytomas the percentage extraction of noradrenaline and adrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…This was to be anticipated since the metabolic pathways of NE and E are identical. However, a comparison of the placental NE and E extraction with that of other organs revealed that the placental tissue occupies a unique position: on passage of Catecholamines through the liver, cardiac and skeletal muscle, the NE extraction rate is invariably lower than that of E [4,13]. The NE concentrations in the renal vein but also in the coronary sinus may even substantially exceed those measured in the arterial (afferent) blood [21,26].…”
Section: Catecholamine Extraction By the Placentamentioning
confidence: 95%
See 2 more Smart Citations
“…This was to be anticipated since the metabolic pathways of NE and E are identical. However, a comparison of the placental NE and E extraction with that of other organs revealed that the placental tissue occupies a unique position: on passage of Catecholamines through the liver, cardiac and skeletal muscle, the NE extraction rate is invariably lower than that of E [4,13]. The NE concentrations in the renal vein but also in the coronary sinus may even substantially exceed those measured in the arterial (afferent) blood [21,26].…”
Section: Catecholamine Extraction By the Placentamentioning
confidence: 95%
“…Fetal arterial E concentrations as an indicator of enhanced release of the hormone from the adrenal medulla in conditions of stress, also demonstrate good correlations with the fetal parameters, although the correlation coefficients were lower than for NE (Figs. [4][5][6]. Unlike NE and E concentrations, the D levels in the umbilical vessels were affected by fetal hypoxia to a minor degree, only.…”
Section: Catecholamine Concentrations In Arterial Andmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, as Folkow et al 21 caution, activities that increase blood pressure in humans usually do so by effecting differentiated rather than generalized increases in sympathetic discharge. Selective increases in cardiac, renal, or splanchnic sympathetic nerve activity could initiate marked hemodynamic changes in hypertensive persons without altering basal venous PNE concentrations, because of hepatic clearance of catecholamines, 22 regional differences in the vascular response to released norepinephrine, or quantitative differences in the adrenergic innervation to these vascular beds. Indeed, PNE correlates well with efferent sympathetic nerve activity to muscle, 23 an organ unlikely to be involved in the pathogenesis of hypertension.…”
mentioning
confidence: 99%
“…22 Furthermore, elevations in renal, splanchnic, or cardiac sympathetic discharge could alter cardiac output or vascular resistance to a much greater extent than PNE concentrations if only a small proportion of circulating norepinephrine comes from these organs. 21 ' 2243 In humans, renal, splanchnic, and cardiac sympathetic nerves together contribute approximately one third of norepinephrine measured in plasma, the lungs another third, and skeletal muscle one fifth.…”
mentioning
confidence: 99%